Pneumotoraks Bilateral Spontan sebagai Manifestasi COVID-19: Laporan Kasus: Laporan Kasus - Sigarlaki, Edgar David; Bunawan, Nur Chandra; Amalia, Nasya; Harlivasari, Annisa Dian; Kenya, Cathleen; Vanto, Yoni; Nugroho, Hardijatmo Muljo (PT Kalbe Farma Tbk., 2026)
Introduction: Spontaneous pneumothorax occurs when part of the lung collapses and air accumulates in the pleural space. The cause of spontaneous pneumothorax is unclear, but this condition may increase the risk of death, particularly if it progresses to tension pneumothorax.COVID-19 is primarily a respiratory disease and may present with various pulmonary manifestations, including rare and severe complications. Case: A 48-year-old woman presented with dyspnea, fever, cough, nausea, and fatigue. Initial rapid antibody testing for SARS-CoV-2 wasnegative. Chest radiograph demonstrated an avascular area in the right lateral hemithorax with medial lung collapse, consistent with right spontaneous pneumothorax. Oxygen therapy and chest tube insertion were performed. Follow up chest x-ray showed resolution of the rightpneumothorax, however, a new pneumothorax developed on the left side. Nasopharyngeal and oropharyngeal swab testing for SARS-CoV-2 was reported positive a few days later, after the patient had died. Discussion: The occurrence of bilateral spontaneous pneumothoraxin this patient suggests lung involvement related to COVID-19 infection. Recognition of atypical pulmonary manifestations is essential, particularly when initial screening tests are negative. Conclusion: COVID-19 can manifest as spontaneous pneumothorax, including bilateral involvement. Early recognition is important to reduce morbidity and mortality.